Population allele frequencies, environmental data, and individual genotypes of Atlantic horse mackerel (Trachurus trachurus) collected across the east Atlantic ocean - Fuentes-Pardo, Angela P.; Farrell, Edward D.; Pettersson, Mats; Grace Sprehn, C.; Andersson, Leif (Uppsala University, 2023)
Pool-wise allele frequencies, environmental data, and individual genotypes used in the manuscript entitled "The genomic basis and environmental correlates of local adaptation in the Atlantic horse mackerel (Trachurus trachurus)" (EVA-2023-003-OA).

In the pool-wise allele frequencies file (tab-separated text gzipped file), pool sample names are indicated in the columns header and SNP markers are in rows (the first two columns indicate the chromosome, CHROM, and base pair position, POS).

In the individual genotype data file (VCF format), rows 1-17 correspond to the general header of the file, row 18 shows the header indicating markers and sample information, genotype data starts in row 19 onwards. The header in row 18 indicates:

Col 1: chromosome (CHROM)

Col 2: position (POS)

Col 3: SNP ID (ID)

Col 4: reference allele (REF)

Col 5: alternative allele (ALT)

Col 6: marker quality (QUAL)

Col 7: filter (FILTER)

Col 8: information (INFO)

Col 9: genotype format (FORMAT)

Col 10-onwards: samples, one per column

In the environmental data file (tab-separated text file), each row corresponds to a pool sample and each column to environmental data such as depth, Longitude (Lon), Latitude (Lat), and eight environmental variables:

Mean depth mean current velocity (m/s) (BO21_curvelmean_bdmean)

Mean depth mean dissolved oxygen (umol/m3) (BO21_dissoxmean_bdmean)

Mean depth mean iron content (umol/m3) (BO21_ironmean_bdmean)

Mean depth mean nitrate (umol/m3) (BO21_nitratemean_bdmean)

Mean depth mean primary productivity (g/m3/day) (BO21_ppmean_bdmean)

Mean depth mean salinity (PSS) (BO21_salinitymean_bdmean)

Mean depth mean temperature (°C) (BO21_tempmean_bdmean)

Mean depth mean temperature range (°C) (BO21_temprange_bdmean)
Keywords: Bioinformatics and computational biology not elsewhere classified; Biological adaptation; Evolutionary ecology; Medical and Health Sciences; Medicin och hälsovetenskap; Ecology; Ekologi; Biological Sciences; Biologi; Bioinformatics (Computational Biology); Bioinformatik (beräkningsbiologi)